HUBUNGAN ANTARA TUNNELING INCENTIVE, BONUS MECHANISM DAN DEBT CONVENANT TERHADAP KEPUTUSAN TRANSFER PRICING DENGAN TAX MINIMIZATION SEBAGAI PEMODERASI - Titik Aryati -; Cicely Delfina Harahap (Jurnal Akuntansi Trisakti, 2021)
The objective of this research was to examine the effect of tunneling incentive, bonus mechanism and debt covenant to transfer pricing. This research also conducted to test the role of tax minimization in moderating the relation between those variables. Research sample was manufacturing companies in consumer goods sector, that registered in Indonesia Stock Exchange 2014-2018. This research use purposive sampling method, with 110 observation data. Analysis method used is multiple linear regression. The result show only Debt covenant that proved can increase firm in transfer pricing. This research was not able to prove tunneling incentive and bonus mechanism influenced the decision of transfer pricing transaction. Tax minimization is not proved moderating the relations between tunneling incentive, bonus mechanism, and debt covenant to transfer pricing transactions.